Safety risk factors in two different types of routine outsourced work: a systematic literature review - Pilbeam, Colin; Denyer, David; Doherty, Noeleen (Taylor & Francis, 2020)
Outsourcing generates risks for client firms but these vary according to the contracted task. This systematic literature review reports on 50 empirical studies that investigate the safety risk factors associated with outsourcing aligning them with the three categories of safety risk factors identified by Underhill and Quinlan in their PDR-Model. By using a 2x2 framework based on the strategic value of the task to the client firm (core or peripheral) and its level of complexity (complex or routine) we could combine studies of outsourced relationships between firms with those between firms and individuals. This demonstrated that there is little empirical evidence available for the safety risk factors associated with complex outsourced tasks. It also showed that routine tasks core to the client business contained risk factors associated with both economic and reward pressure and disorganization. Finally, safety risk factors associated with routine peripheral tasks were mainly due to economic and reward pressures in firm-to-individual contracting, but due to disorganization in firm-to-firm contracting.
Keywords: Systematic literature review; Outsourcing; Safety Risk; Contractor